Clinical practice in vesicoureteral reflux with respect to EAU guidelines: A multicenter study - ŞEKERCİ, ÇAĞRI AKIN (WILEY, 2021)
Purpose We designed a multicenter, retrospective study to investigate the current trends in initial management of reflux with respect to European Association of Urology (EAU) Guidelines in Urology clinics of our country. Materials and methods The study group consisted of 1988 renal units (RU) of 1345 patients treated surgically due to vesicoureteral reflux (VUR) (between years 2003 and 2017) in nine different institutions. Patients were divided into two groups according to time of initial treatment and also grouped according to risk factors by EAU guidelines on VUR. Results In this series, 1426 RUs were treated initially conservatively and 562 RUs were initially treated with surgery. In initially surgically treated group, success rates of surgery decreased significantly in low and moderate risk groups after 2013 (P = .046, P = .0001, respectively), while success rates were not significantly different in high risk group (P = .46). While 26.6% of patients in low risk group were initially surgically treated before 2013, this rate has increased to 34.6% after 2013, but the difference was not statistically significant (P = .096). However, performing surgery as the initial treatment approach increased significantly in both moderate and high risk groups (P = .000 and P = .0001, respectively) after 2013. Overall success rates of endoscopic treatments and ureteroneocystostomy (UNC) operations were 65% and 92.9% before 2013 and 60% and 78.5% after 2013, respectively. Thus, the overall success rate for surgery was 72.6%. There was significant difference between success rates of UNC operations before and after 2013 (P = .000), while the difference was not significant in the injection group (P = .076). Conclusion Current trends in management of reflux in our country do not yet follow the EAU guidelines on VUR in low and moderate risk groups despite these reliable and accepted guidelines were expected to influence our daily approach.
Keywords: URINARY-TRACT-INFECTION; ANTIBIOTIC-PROPHYLAXIS; URETERAL REIMPLANTATION; SURGICAL-MANAGEMENT; SWEDISH REFLUX; CHILDREN; TRIAL